Experimental investigation of the behavior of concrete beams containing recycled materials reinforced with composite rebars - Ramin Jafari; Mohammad Hadi Alizadeh Elizei; Masuod Ziaei; Reza Esmaeil Abadi (Materiales de Construccion, 2023)
The application of various Fiber Reinforced Polymer (FRP) composite materials is very widespread in the world. The use of recycled materials in concrete, can improve some of the mechanical properties of concrete. In this laboratory research, the behavior of reinforced concrete beams with composite rebars with glass fibers made of concrete containing recycled materials such as glass, rubber and micro-silica with different mixing plans has been investigated. These mixing plans are such that recycled glass and rubber aggregates have replaced a percentage of fine and coarse concrete aggregates, and glass powder and micro-silica have also replaced a percentage of concrete cement. The results showed that the replacement of coarse rubber, glass powder, and micro-silica in concrete materials increases the bending strength and ductility of concrete beam. In examining the microstructure of concrete by Scanning Electron Microscope (SEM) the adhesiveness of the rubber Interfacial Transition Zone (ITZ) in concrete was suitable.